EDITORIAL BOARD - Wiguna, Putu Perdana Kusuma (International Journal of Biosciences and Biotechnology; Vol 9 No 2 (2022): INTERNATIONAL JOURNAL OF BIOSCIENCES AND BIOTECHNOLOGY, 2022)
Editorial Board IJBB Vol. 9 No. 1